Payments for Environmental Services: A New People Centric Approach for Biodiversity Conservation in Nepal - Chalise, Lina (The Initiation, 2010)
Payment for Environmental Services (PES) in its preliminary stage is gaining much attention. The worth of many valuable environmental services is undermined from centuries due its free access. But now with the advancing time the blind conservation practices seem to be unreal. Thus, PES mechanism provides an attractive and convincing package in conservation and valuation of most of the indirect services of environment. This is a review article based on the introductory queries on emerging issue of valuation of environmental services via PES mechanism. Key Words: Environmental services, Global biodiversity, Conservation practices DOI: 10.3126/init.v2i1.2529 The Initiation Vol.2(1) 2008 pp99-103